EFEKTIFITAS PEER EDUCATOR DALAM PENANGGULANGAN PENYALAHGUNAAN NARKOTIKA PADA REMAJA SMU N KEPENUHAN HULU KECAMATAN KEPENUHAN KABUPATEN ROKAN HULU. - Wulandari, Sri; Handayani, Eka Yuli (Jurnal Martenity and Neonatal, 2019)
Drug abuse and distribution dark was a serious problem alarming international.The unodc, indonesia currently in the first place in the number of suspected drug. aseanThe survey by the agency years 2017 total penyalahguna 3.376.115, the narcotic and prevalence of highest is in the educated middle class. this is concernedThe united nations officion on drugs and crime ( unodc ) stated that 27 0,6 million people or percent of the population age this year is 15-64. suffers with consumption of drugs Drug abuse endangers life penyalahguna, and others drugs abuse, negatively impact on the physical psychological, social and spiritual so this had an impact on the outcome. learning achievementsThe impact is slow work, careless, work lost confidence, apathetic, pengkhayal, be vicious and brutal behavior. Difficult to concentrate, tend to hurt themselves. even suicideFormer needed.The purpose of this research is to find the effectiveness of peer educator conducted by former users and nonusers narcotic drugs abuse prevention of juvenile smun 1 fullness. upstreamThe study used is quasi experiment is pretest-postes comparison with, group for the purpose of knowing the difference the effectiveness of peer educator conducted by former drugs users and not using drugs abuse prevention of juvenile smun 1 fullness. upstreamWith the total sample 80, one the group 40 information given by former users of narcotics and 40 one group who were given information by not using. narcotics To be performed by steps:1.The preparatory stage ( making ) module.2.The election3. peer educatorPhase of the Topicresearch objectives made a pact and exercise peer educator, and evaluate the training and the rest of the data collection will intervene in teenagers peer educator education health by former drug users and nonusers.The outer covering of the research is a scholarly article was published in the national and not accredited issn ( maternity and neonatal and issn 2302-0806 ), article was published in national, proceeding research will be presented (Keynote Speaker /Invited) invited the keynote speaker at a national scientific.The readiness of technology ( TKT ) the formulation of the concept is applying the knowledge and development of the community in berprilaku healthy to empower society itself especially the youth prevention as drugs abuse by the provision of information and genuine true keywords